2002
DOI: 10.1111/j.1572-0241.2002.07066.x
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole-associated microscopic colitis: a case series1

Abstract: Lansoprazole is a potent proton pump inhibitor that has been well tolerated with minimal serious adverse events. One of the most commonly reported side effects is diarrhea in 3-8% of study patients. During 1997, approximately 850 veterans at our institution had their proton pump inhibitor converted from omeprazole to lansoprazole because of a formulary change. A number of patients subsequently developed chronic watery diarrhea. While evaluating six of these patients, we discovered microscopic colitis that reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…Of these patients, 91% had resolution of their diarrhoea when placed on omeprazole. Microscopic colitis has been described in association with lansoprazole, and resolved after discontinuation of the drug 18 . While the incidence of diarrhoea in our study appears low (24/3703=0.65%), this number is probably a gross underestimation of the total number of patients on lansoprazole at our institutions who have had diarrhoea in association with a proton pump inhibitor.…”
Section: Discussioncontrasting
confidence: 65%
“…Of these patients, 91% had resolution of their diarrhoea when placed on omeprazole. Microscopic colitis has been described in association with lansoprazole, and resolved after discontinuation of the drug 18 . While the incidence of diarrhoea in our study appears low (24/3703=0.65%), this number is probably a gross underestimation of the total number of patients on lansoprazole at our institutions who have had diarrhoea in association with a proton pump inhibitor.…”
Section: Discussioncontrasting
confidence: 65%
“…In a case-control study of 31 patients with collagenous colitis, 61% had recently used NSAIDs compared with 13% of age and sex-matched controls with irritable bowel syndrome or diverticular disease (27). Lansoprazolerelated microscopic colitis has been reported in two other studies (29,30). In addition, Baert et al, reported that 7 of 28 patients with collagenous colitis were taking lansoprazole or omeprazole at the time of diagnosis (14).…”
Section: Discussionmentioning
confidence: 99%
“…While CC has been described as an unexplained inflammatory bowel disease, drug-induced CC and possible involvement of autoimmune mechanisms in the onset of CC have been reported [5,6,7]. In Japan, most of the recently reported cases had a history of use of LPZ, a type of PPI, and some studies have suggested that endoscopically documented longitudinal linear lacerations of the mucosa might be the cause of CC [8,9].…”
Section: Discussionmentioning
confidence: 99%